Making Implementation Deed Electronically Based on Law of Notary - Yudha Priyo Kuspratomo; Lailatul Nur Hasanah; Sri Endah Wahyuningsih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) To know and analyze the mechanisms of electronic deed made by the notary. 2) To analyze the obstacles faced by the notary in the manufacture of electronic certificates. The method used in this empirically is sociological juridical data used in this study are primary data and secondary data, primary data obtained by conducting interviews with Indonesian Notary Association, and secondary data obtained by reviewing book. Found of data analysis concluded that: 1) the Indonesian Notary Association until now was not serious to realize implementation electronically authentic deed. With electronic media, notaries become more efficient administration. 2) Barriers cyber Notary the notary system management. Managed the Ministry of Justice and Human Rights of the Republic of Indonesia or the Indonesian Notaries Association organization. Because the office of notary is an independent, preferably Indonesian Notary Association has its own system that will manage the cyber Notary and can be used by all notaries Indonesia. Harmonization Act as a way out for the development of cyber Notary in Indonesia. Keywords: Deed Electronics; Cyber Notary; UUJN.